(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the critical role of accurate translation in legal documents and its direct impact on judicial outcomes and the development of international law. In an increasingly globalized legal environment, cross-border disputes, international treaties, and transnational litigation rely heavily on precise linguistic interpretation. Even minor translation errors may lead to significant misinterpretations of legal norms, contractual obligations, and procedural rights. The study analyzes common types of translation errors, including semantic inaccuracies, terminological inconsistencies, and cultural misinterpretations. It also explores how such errors influence court decisions, potentially leading to unjust rulings or prolonged legal disputes. Special attention is given to the role of certified translators, legal experts, and institutional frameworks that aim to minimize risks associated with linguistic ambiguity. Furthermore, the article highlights notable cases where translation mistakes have altered judicial outcomes or affected international agreements. It argues that improving translation standards, adopting unified legal terminology, and enhancing cooperation between linguists and legal professionals are essential for ensuring fairness and consistency in legal systems.